Sustainable effect of individualised sun protection advice on sun protection behaviour: a 10-year follow-up of a randomised controlled study in primary care - Hedevik, Henrik (BJGP Open, 2019)
BACKGROUND: In the light of increasing skin cancer incidences worldwide, preventive measures to promote sun protection in individuals with risky sun habits have continued relevance and importance. AIM: To report the long-term effect of individualised sun protection advice given in primary health care (PHC), on sun habits and sun protection behaviour. DESIGN & SETTING: In 2005, 309 PHC patients were enrolled in a randomised controlled study performed in a Swedish PHC setting. METHOD: At baseline, the study participants completed a Likert scale-based questionnaire, mapping sun habits, propensity to increase sun protection, and attitudes towards sun exposure, followed by randomisation into three intervention groups, all receiving individualised sun protection advice: in Group 1 (n = 116) by means of a letter, and in Group 2 (n = 97) and 3 (n = 96) communicated personally by a GP. In Group 3, participants also underwent a skin ultraviolet-sensitivity phototest, with adjusted sun protection advice based on the result. A repeated questionnaire was administered after 3 and 10 years. RESULTS: Statistically significant declines were observed in all groups for sun exposure mean scores over time. When using a cumulative score, according to the Sun Exposure and Protection Index (SEPI), significantly greater decrease in SEPI mean score was observed in Groups 2 and 3 (GP), compared to Group 1 (letter); P<0.01. The addition of a phototest did not enhance the effect of the intervention. CONCLUSION: Individualised sun protection advice mediated verbally by the GP can lead to sustained improvement of sun protective behaviour.